(3bUjOI dGHf GdNjGW efbhdI ef NQjOI GdbUQ ddYeGO GdcGJHs - (3GHf GdNjGW, CMeO Hf eMeO Hf Ydj, J(B517(3g`s
(3ChdgG (B:s
(3NPG ef UHG fLO CeGfG dbdHg (B*** (3abO cGO QjGgG jWjQ HdHgs
(3BNQgG (B:s
(3adG Xd EdG ef LfGHc QhVg (B*** (3hdG HGfJ EdG aj afGFc eGDgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 214s
(3eYLe GdeDdajf(B: 1 / 283s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs